Multi-omics integration and machine learning define an iron-sulfur cluster/zinc-binding protein prognostic signature in esophageal squamous cell carcinoma - Wenhuan Chen; Tongtong Chen; Zhixuan Li; Wan Lin; Zefeng Xie; Hansheng Wu; Liyan Xu; Enmin Li; Hefeng Zhang; Yinwei Cheng (Mammalian Genome, 2026)

Quasi-Newton method based finite-time fuzzy tracking control for uncertain unmanned surface vehicles: Indirect and direct approaches - Min Ma; Zefeng Lin; Tong Wang; Tieshan Li (Ocean Engineering, 2026)

Twistors-based anti-unwinding control of spacecraft via the fully actuated system approach - Dongyan Jin; Shuqian Feng; Zefeng Lin; Wenqiang Ji; Tong Wang; Jianbin Qiu (Advances in Space Research, 2026)

Bioaccumulation and trophic transfer of phthalate esters in mangrove food web - Jianan Liu; Yuyan Liu; Siwen Chen; Rui Xu; Haofeng Liu; Zefeng Wang; Xianbiao Lin; Ye Li; Min Liu (Marine Pollution Bulletin, 2026)

Catalytic application of coal liquefaction bottom residue in co-hydrocracking with MRAR under catalyst-free conditions - Zefeng Miao; Tengfei Yang; Congcong Liu; Yao Jiang; Lin Meng; Huitao Liu; Xiaobin Wang; Chuan Li (Fuel, 2026)

How the Carbon Neutrality Process Moves Forward: a Global-scale Evaluation from Past To Future - Yicheng Yang; Zefeng Qi; Hongxuan Fu; Shuan Peng; Nihed Benani; Xi Cheng; Jian Lin Chen; Pingjian Yang; Guozhu Mao (International Journal of Environmental Research, 2025)

Bioremediation of heavy metals by mangrove rhizosphere microbes: Extracellular adsorption mechanisms and enhanced performance of immobilized Aestuariibaculum sp. JKB11 - Zuye Zhang; Xiaojun Huang; Si Chen; Ying Xu; Yue Qiao; Runmei Jia; Song Zhang; Wenting Lin; Xian Jiao; Mo Shi; Huirong Chen; Zhipeng Guo; et al. (Journal of Hazardous Materials, 2025)

Water effect on ignition delay times of ethanol/iso-octane mixtures at elevated pressures - Xue Jiang; Tianqi Zhang; Zefeng Lin; Yingjia Zhang; Zuohua Huang; Wei Zhu; Linxun Xu; Suxian Xu (Fuel, 2025)

Design and characterization of AgC nanocomposite frameworks in porous silicon anodes for high-performance solid-state batteries - Baoguo Zhang; Lin Wu; Xiaoyu Yang; Jingwang Li; Zefeng Yuan; Zihao Dang; Rongsheng Chen; Ying Liu; Ya Hu (Chemical Engineering Journal, 2025)

Enhancing the thermal conductivity of carbon fiber composites by unzipping MWCNTs into GNRs through flash Joule heating - Lin Li; Zefeng Yang; Yun Liao; Lei Deng; Shangang Zhou; Keqiao Zeng; Wenfu Wei (Chemical Engineering Journal, 2025)

Effects of water addition on the laminar burning velocities of ethanol/iso-octane mixtures - Tianqi Zhang; Xue Jiang; Zefeng Lin; Zuohua Huang; Wei Zhu; Linxun Xu; Suxian Xu (Fuel, 2025)

Rapid penetrating inactivation and disinfection through ice layers by light-condensed deep ultraviolet LED irradiation - Lucheng Yu; Peng Shen; Zefeng Lin; Shini Yang; Maowei Yang; Yaxiao Lou; Shiqiang Lu; Feiya Xu; Shengrong Huang; Xueqiong Sun; Jiamin He; Huachun Wang; et al. (Journal of Photochemistry and Photobiology B: Biology, 2025)

Unequal transfer and its policy implications of carbon emissions and economic benefits embodied among Central Plains urban agglomeration - Shuan Peng; Min Chen; Zefeng Qi; Nihed Benani; Tao Wang; Xuefang Wu; Xi Cheng; Jian Lin Chen; Guozhu Mao; Pingjian Yang (Urban Climate, 2024)

Effects of urbanization and topography on thermal comfort during a heat wave event: A case study of Fuzhou, China - Zefeng Zheng; Xinlu Lin; Li Chen; Chao Yan; Ting Sun (Sustainable Cities and Society, 2024)

Corrigendum to “Estimation and potential ecological risk assessment of multiphase PAEs in mangrove wetlands in Dongzhai Harbor, Hainan” [Sci. Total Environ. 870 (2023) 161835] - Lin Wang; Yuyan Liu; Yiwei Zhang; Siwen Chen; Niuniu Zhang; Zefeng Wang; Haofeng Liu (Science of The Total Environment, 2023)

Estimation and potential ecological risk assessment of multiphase PAEs in mangrove wetlands in Dongzhai Harbor, Hainan - Lin Wang; Yuyan Liu; Yiwei Zhang; Siwen Chen; Niuniu Zhang; Zefeng Wang; Haofeng Liu (Science of The Total Environment, 2023)

Patent mining on soil pollution remediation technology from the perspective of technological trajectory - Zefeng Qi; Yixin Han; Sandylove Afrane; Xi Liu; Mingqi Zhang; John Crittenden; Jian Lin Chen; Guozhu Mao (Environmental Pollution, 2023)

Impact of the COVID-19 on electricity consumption of open university campus buildings – The case of Twente University in the Netherlands - Sheng Xu; Bin Cheng; Zefeng Huang; Tao Liu; Yuan Li; Lin Jiang; Wei Guo; Jie Xiong (Energy and Buildings, 2023)

Biodynamic responses of adolescent idiopathic scoliosis exposed to vibration - Shaowei Jia; Liying Lin; Hufei Yang; Junde Xie; Zefeng Liu; Tianyou Zhang; Jie Fan; Li Han (Medical & Biological Engineering & Computing, 2023)

Numerical Investigation to the Effect of Suction-Induced Seepage on the Settlement in the Underwater Vacuum Preloading with Prefabricated Vertical Drains - Shu Lin; Dengfeng Fu; Zefeng Zhou; Yue Yan; Shuwang Yan (Journal of Marine Science and Engineering, 2021)
Vacuum preloading combined with prefabricated vertical drains (PVDs) has the potential to improve the soft sediments under water, however, its development is partly limited by the unclear understanding of the mechanism. This paper aims to extend the comprehension of the influential mechanism of overlapping water in the scenario of underwater vacuum preloading with PVDs. The systematic investigations were conducted by small strain finite element drained analyses, with the separated analysis schemes considering suction-induced consolidation, seepage and their combination. The development of settlement in the improved soil region and the evolution of seepage flow from the overlapping water through the non-improved soil region into improved zone are examined in terms of the build-up of excess pore pressure. Based on the results of numerical analyses, a theoretical approach was set out. It was capable to estimate the time-dependent non-uniform settlement along the improved soil surface in response to the combined effects of suction-induced consolidation and seepage. The difference of underwater and onshore vacuum preloading with PVDs is discussed with some practical implication and suggestion provided.

Logistic model-based genetic analysis for kernel filling in a maize RIL population - Shuangyi Yin; Pengcheng Li; Yang Xu; Lin Xue; Derong Hao; Jun Liu; Tiantian Yang; Zefeng Yang; Chenwu Xu (Euphytica, 2018)